Regional Differences in the Cerebral Blood Flow Velocity Response to Hypobaric Hypoxia at High Altitudes. Issue 11 (November 2015) - Feddersen, Berend; Neupane, Pritam; Thanbichler, Florian; Hadolt, Irmgard; Sattelmeyer, Vera; Pfefferkorn, Thomas; Waanders, Robb; Noachtar, Soheyl; Ausserer, Harald
Symptoms of acute mountain sickness (AMS) may appear above 2, 500 m altitude, if the time allowed for acclimatization is insufficient. As the mechanisms underlying brain adaptation to the hypobaric hypoxic environment are not fully understood, a prospective study was performed investigating neurophysiological changes by means of near infrared spectroscopy, electroencephalograpy (EEG), and transcranial doppler sonography at 100, 3, 440 and 5, 050 m above sea level in the Khumbu Himal, Nepal. Fourteen of the 26 mountaineers reaching 5, 050 m altitude developed symptoms of AMS between 3, 440 and 5, 050 m altitude (Lake-Louise Score ≥ 3). Their EEG frontal beta activity and occipital alpha activity increased between 100 and 3, 440 m altitude, i.e., before symptoms appeared. Cerebral blood flow velocity (CBFV) in the anterior and middle cerebral arteries (MCAs) increased in all mountaineers between 100 and 3, 440 m altitude. During further ascent to 5, 050 m altitude, mountaineers with AMS developed a further increase in CBFV in the MCA, whereas in all mountaineers CBFV decreased continuously with increasing altitude in the posterior cerebral arteries. These results indicate that hypobaric hypoxia causes different regional changes in CBFV despite similar electrophysiological changes.